Direct Synthesis of Highly Designable Hybrid Metal Hydroxide Nanosheets by Using Tripodal Ligands as One‐Size‐Fits‐All Modifiers. Issue 21 (20th February 2017) - Kuroda, Yoshiyuki; Koichi, Tatsuyuki; Muramatsu, Keisuke; Yamaguchi, Kazuya; Mizuno, Noritaka; Shimojima, Atsushi; Wada, Hiroaki; Kuroda, Kazuyuki
Abstract: Invited for the cover of this issue is the group of Yoshiyuki Kuroda and Kazuyuki Kuroda at the Waseda University in Tokyo. The image depicts how the production of diverse metal hydroxide nanosheets can be standardized in the same way as Sushi. Read the full text of the article at10.1002/chem.201605698 . Abstract : " The future goal of this study will be the production of designed nanosheets which satisfy the demands of functional devices, in the same way as a Sushi master makes flavored Sushi that fits the customer's taste ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 5023 ff. (DOI:10.1002/chem.201605698 ).